Сlinical features of changes in the microcirculation system among children with allergic rhinitis, depending on the severity of dysfunction of the autonomic nervous system - N. S. Tataurschikova; P. V. Berezhansky (Медицинская иммунология)
In recent years, there has been an increase in the prevalence of allergic diseases in children. Allergic rhinitis (AR) ranks first among other allergic diseases in terms of prevalence and impact on the health and quality of life patients. In various countries of the world, according to various sources, from 10 to 40% of the population suffers. Allergic rhinitis is a serious medical, social and economic problem. In addition, allergic rhinitis, especially with multiple sensitization and insufficiently controlled course, is an independent risk factor for recurrence of respiratory infections and the development of bronchial asthma, and also significantly reduces the quality of life patients.AR is a multifactorial disease in the development of which many factors play a role. The basis of the pathological process in AR is IgE--dependent mucosal inflammation, which is realized under the influence of specific and nonspecific mechanisms and has a Th2 character. The tissues and organs involved in the process determine the formation of complex mechanisms of interaction between the immune, microcirculatory and autonomic nervous systems.The inflammatory process in AR is characterized by a number of features, for example, the presence of minimal persistent inflammation and the priming effect, which in turn is a predisposing factor for the clinical onset and progression of AR. Microcirculatory mechanisms are of great pathogenetic significance in the development of allergic inflammation, including in AR.Depending on the leading pathognomonic trait, it is now customary to distinguish individual phenotypes and endotypes of AR.The phenotype covers the clinically significant properties of AR, but does not reveal the detailed mechanisms of its development, on the basis of which a personalized algorithm for prevention, treatment and prognosis can be created.And the autonomic nervous system is responsible for setting links between the body, ambient and internal environment through the regulation of metabolism, functioning of organs and tissues based on changes in this environment; it also provides the integration of all organs into a single whole acting as one of the main body’s adaptive systems.Since the autonomic nervous system governs the body and homeostasis uniting separate pathogenetic links of disease progression and sets the basis for structural and functional unity. In light of this, the failure of neuroregulatory mechanisms takes the lead among the causes of systemic changes in the microvasculature, which, in turn, reflects general pathogenetic processes in the body. The regulatory mechanism is implemented through nerves and reflexes by different neurohumoral factors, their nature has been studied under experimental conditions and is beyond doubt to date.The study of the main indicators of microcirculation and the autonomic nervous system among children with allergic rhinitis in various combinations with concomitant pathology will highlight new AR phenotypes and select an individual treatment and rehabilitation plan for these children.